Hilando La Memoria Ancestral Mosqueruna: Sistematización de una Experiencia Artístico – Pedagógica Con Integrantes del Grupo Infantil de la Escuela De Formación en Danza Del Municipio De Mosquera – Cundinamarca (2017)
This research has as main objective to analyze the process of creation of the joint assembly "Spinning the ancestral memory Mosqueruna" from the reconstruction of the experience lived with the members of the children's group of the school of dance training in the municipality of Mosquera.